Prevalence of Anemia among Women: A Hospital- Based Study in Eastern Nepal - Sinha, Amar Kumar; Manandhar, Naresh (Janaki Medical College Journal of Medical Science, 2020)
Background and Objectives: Prevalence of anemia is a common health problem among the women particularly in developing countries. The purpose of our study is to determine the prevalence of anemia among women in eastern Nepal. The study is planned to find out the prevalence of anemia among the women in eastern Nepal. Material and Methods: Retrospective study was conducted among the women in between group of age 20->70 years during Dec 2015 to Aug.2016. Anemia was classified as per the WHO guideline i.e. Mild, moderate and severe. Results: Out of 877 women included in the study, 512 (58.4%) women were diagnosed anemic. The highest prevalence of anemia 61.5% & 60.6% were found at the age group of 50-59 and 20-29 yrs respectively among the anemic patients. Mean and SD (Std. deviation) of hemoglobin and age was 10.21 ± 1.45 gm/dl and 35.59 ± 14.14 yrs of the anemic populations respectively. Conclusion: It is concluded that the anemia still constitutes a health problem among women with the present prevalence 74.2% in Dalit caste in eastern Nepal. Further research is recommended to identify the specific risk factors of anemia in women.